2010
DOI: 10.1186/1472-6963-10-139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors affecting home blood pressure documentation in routine clinical care: a retrospective study

Abstract: BackgroundHome blood pressure (BP) is closely linked to patient outcomes. However, the prevalence of its documentation has not been examined. The objective of this study was to analyze the prevalence and factors affecting documentation of home BP in routine clinical care.MethodsA retrospective study of 142,973 encounters of 9,840 hypertensive patients with diabetes from 2000 to 2005 was performed. The prevalence of recorded home BP and the factors associated with its documentation were analyzed. We assessed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(30 reference statements)
1
2
2
Order By: Relevance
“…Previous studies among general patients with hypertension (primary care or community settings) have shown inconsistent results. Some studies reported that patients with a higher education level, higher income, male sex and a younger age were more likely to adopt HBPM [2,13,21,22], while other studies found higher HBPM use in older adults [14,22,23]. In this study, sex negatively affected adoption of HBPM, and older patients were more likely to use HBPM.…”
Section: Resultscontrasting
confidence: 48%
“…Previous studies among general patients with hypertension (primary care or community settings) have shown inconsistent results. Some studies reported that patients with a higher education level, higher income, male sex and a younger age were more likely to adopt HBPM [2,13,21,22], while other studies found higher HBPM use in older adults [14,22,23]. In this study, sex negatively affected adoption of HBPM, and older patients were more likely to use HBPM.…”
Section: Resultscontrasting
confidence: 48%
“…Previous studies among general patients with hypertension (primary care or community settings) have shown inconsistent results. Some studies reported that patients with a higher education level, higher income, male sex and a younger age were more likely to adopt HBPM [2,15,22,23], whereas other studies found higher HBPM use in older adults [16,23,24]. In this study, no difference in HBPM was found between males and females, and older participants were more likely to use HBPM.…”
Section: Discussioncontrasting
confidence: 74%
“…This is consistent with prior investigations that showed that a large fraction of medical information is recorded only in narrative (e.g. provider notes) but not structured data [35,36,37]. While manual chart review of large numbers of records to abstract information from narrative documents is not always feasible, natural language processing technology can allow for rapid and accurate identification of critical pieces of information [38].…”
Section: Discussionsupporting
confidence: 71%